Increasing the Knowledge and Confidence of Mothers in Caring for Low Birth Weight Babies Through Education from the Maternal and Child Health Handbook - Sugiarti, Sugiarti; Rustina, Yeni; Efendi, Defi (Jurusan Keperawatan FIKES UNSOED, 2020)
Having a Low Birth Weight (LBW) is one of the risk factors that may lead to stunting in children under five years old. An education program based on the Maternal and Child Health handbook (MCH) for the first 1000 days of a child’s life is one way to prevent the impact of stunting by improving the mothers’ knowledge and self-confidence to look after LBWB. The study is designed along the line of pre-post quasi-experimental research with a control group, involving 69 samples of mothers with LBWB that match the predetermined criteria. Twenty three of these mothers whose babies were cared for in the perinatology ward were provided with instructions from the MCH handbook, another group of 23 mothers received the same instructions with additional audiovisual media from a mobile application, and the remaining 23 mothers only received verbal instructions in the ward. The data were analyzed using the Paired t-test/Wilcoxon and Kruskall-Wallis tests. The analysis revealed that the MCH handbook based instruction provided a significant boost on the score of mother’s knowledge and confidence, before and after they have received the instructions, both in the group that received the MCH handbook based instruction (p<0.001) and the group that received their instructions from a mobile application (p<0.001). Additional instructions using audiovisual media from a mobile application also provided a significant boost to the knowledge score, and therefore the post-education score of the mothers in this group was higher than in the other two groups (p<0.001). Mother’s knowledge of the provision of care for LBWB can therefore be optimized through education, discussion, and the use of technology as an instructional medium to complement the use of the MCH handbook.